THE VALUE OF THE BLOOD PROCALCITONIN-TO-ALBUMIN RATIO IN PREDICTING 28-DAY MORTALITY IN SEPSIS AT THONG NHAT HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate the association between the procalcitonin-to-albumin ratio and disease severity scores (SOFA, APACHE II, lactate) and to assess its prognostic value for 28-day mortality in septic patients.Methods: A prospective cohort study was conducted from August 2023 to August 2025, including 196 patients admitted to the Intensive Care Unit of Thong Nhat Hospital. Procalcitonin and albumin were measured within 24 hours after sepsis diagnosis to calculate procalcitonin-to-albumin ratio.Results: The median age was 70 years, and 48% were male. The respiratory tract was the primary source in 45%, and blood culture positivity was 26%. Non-survivors had higher SOFA, APACHE II, procalcitonin, and lactate, but lower albumin and pH. Procalcitonin-to-albumin ratio correlated positively with lactate (r = 0.75), SOFA (r = 0.78), and APACHE II (r = 0.82), all p < 0.001. In multivariate analysis, procalcitonin-to-albumin ratio independently predicted 28-day mortality (OR = 1.339, 95% CI: 1.190-1.508, p < 0.001). The AUC for mortality prediction was 0.85 (cutoff 4.05; sensitivity 94.5%; specificity 60.9%).Conclusion: Procalcitonin-to-albumin ratio reflects both inflammation and malnutrition, correlates with sepsis severity, and provides strong prognostic value for 28-day mortality. It is a simple, feasible marker that may be widely applied in clinical practice.
Keywords: Procalcitonin, albumin, mortality, sepsis.